2018
DOI: 10.1080/15287394.2018.1460787
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrospermopsin toxicity in mice following a 90-d oral exposure

Abstract: Cylindrospermopsin (CYN) is a toxin associated with numerous species of freshwater cyanobacteria throughout the world. It is postulated to have caused an episode of serious illnesses in Australia through treated drinking water, as well as lethal effects in livestock exposed to water from farm ponds. Toxicity included effects indicative of both hepatic and renal dysfunction. In humans, symptoms progressed from initial hepatomegaly, vomiting, and malaise to acidosis and hypokalemia, bloody diarrhea, and hyperemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 70 publications
2
23
0
Order By: Relevance
“…Though several papers have focused on mammalian toxicity due to its direct relevance to humans (Antal et al, 2011;Baker et al, 2001;Basu et al, 2018;Bazin et al, 2010;Chernoff et al, 2018;Fastner et al, 2003;Fonseca et al, 2014;Gacsi et al, 2009;Kittler et al, 2016), limited in vivo mechanistic toxicity work with aquatic species has been performed. Based on our literature review, eleven studies have reported mechanistic toxicity information for CYN exposure in aquatic organisms (Table 2 of Supplemental Materials).…”
Section: Aquatic Toxicity Of Cynmentioning
confidence: 99%
“…Though several papers have focused on mammalian toxicity due to its direct relevance to humans (Antal et al, 2011;Baker et al, 2001;Basu et al, 2018;Bazin et al, 2010;Chernoff et al, 2018;Fastner et al, 2003;Fonseca et al, 2014;Gacsi et al, 2009;Kittler et al, 2016), limited in vivo mechanistic toxicity work with aquatic species has been performed. Based on our literature review, eleven studies have reported mechanistic toxicity information for CYN exposure in aquatic organisms (Table 2 of Supplemental Materials).…”
Section: Aquatic Toxicity Of Cynmentioning
confidence: 99%
“…exposure [62], male mice were more sensitive than females to CYN administered i.p. [63]. CYN exposure doses (75, 23.7, and 7.5 µg/kg b.w.)…”
Section: Discussionmentioning
confidence: 99%
“…These in vivo results are in accord with other in vivo and in vitro studies where MC-LR induced liver injury through the production of ROS among other mechanisms [ 74 , 79 , 80 ]. Hepatocyte injury was also observed after CYN exposure in rats [ 42 , 43 , 81 ] and mice [ 41 , 63 , 82 , 83 ], with its severity increasing with the dose [ 37 , 63 , 82 , 83 , 84 ]. On the other hand, a variable number of multinucleated hepatocytes was observed in the high and medium-dosed groups (23.7 + 237 or 75 + 750 μg/kg b.w.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions also occurred in the renal medulla and include thinning of the outer stripe and the presence of intraluminal protein in the inner stripe and inner medulla. 16…”
Section: The Occurrence and Toxicological Effects Of Freshwater Cyanomentioning
confidence: 99%